The legacy of the Malay letter = Warisan warkah Melayu - Gallop, Annabel Teh; Kratz, Ernst Ulrich (Published by the British Library for the National Archives of Malaysia, 1994)
Displayed and translated in this exhibition catalogue are 100 Malay letters. They provide a resource for the political, diplomatic and economic history of the Malay archipelago. Traditional Malay manuscript guides to letter-writing, and literary and historical texts are also presented.